Preoperative Folate Receptor-Positive Circulating Tumor Cell Level Is a Prognostic Factor of Long Term Outcome in Non-Small Cell Lung Cancer Patients - Li, Hang; Li, Bin; Pan, Yunjian; Zhang, Yang; Xiang, Jiaqing; Zhang, Yawei; Sun, Yihua; Yu, Xiang; He, Wei; Hu, Hong (Frontiers in Oncology, 2021)
Background: Surgical resection is often the preferred treatment option for non-small cell lung cancer (NSCLC). Despite successful resection, a significant portion of patients eventually develop recurrence and/or metastasis, which is associated with poor prognosis. Biomarkers that are predictive of prognosis after surgical resection can help better monitor and treat patients promptly so as to improve survival. Development of such biomarkers is continuously sought after in clinical practice. In this study, we evaluated one potential candidate biomarker, the folate receptor-positive circulating tumor cell (FR+CTC), by investigating its prognostic and predictive significance in NSCLC patients who have received surgery. Methods: In this prospective, observational study, we enrolled NSCLC patients who were eligible to receive surgical resection. Prior to operation, peripheral blood was collected from each patient for an FR+CTC analysis. FR+CTCs were isolated by negative enrichment using immunomagnetic beads to deplete leukocytes and then quantitatively detected by a ligand-targeted polymerase chain reaction (PCR) method. These patients were then given standard care and were actively followed up for up to seven years. At the end of the seven-year follow-up period, the association between the FR+CTC level and the prognosis in these patients was evaluated. Results: Between patients with low- and high-risk pathological adenocarcinoma subtypes, the preoperative FR+CTC level was significantly different (P=0.028). Further, patients having low preoperative FR+CTC level had longer relapse-free survival (RFS) and overall survival (OS) than those having high preoperative FR+CTC level (RFS: not reached vs. 33.3 months, P=0.018; OS: not reached vs. 72.0 months, P=0.13). In a multivariate COX regression analysis, FR+CTC level (HR, 4.10; 95% CI, 1.23-13.64; P=0.022) and pathological stage (HR, 3.16; 95% CI, 1.79-10.14; P=0.0011) were independent prognostic factors of poorer RFS. In addition, FR+CTC level together with adenocarcinoma subtypes provide additional information on risk for disease recurrence compared with FR+CTC or adenocarcinoma subtype alone. Conclusion: Our study demonstrated that the preoperative FR+CTC level was a potential predictor for the prognosis of NSCLC patients receiving surgical resection. Further, while preoperative FR+CTC level correlates with primary tumor invasion/proliferation characteristics, its prognostic value supplements that of these conventional pathological features.